2022
DOI: 10.1161/circheartfailure.121.009521
|View full text |Cite
|
Sign up to set email alerts
|

Defects in the Proteome and Metabolome in Human Hypertrophic Cardiomyopathy

Abstract: BACKGROUND: Defects in energetics are thought to be central to the pathophysiology of hypertrophic cardiomyopathy (HCM); yet, the determinants of ATP availability are not known. The purpose of this study is to ascertain the nature and extent of metabolic reprogramming in human HCM, and its potential impact on contractile function. METHODS: We conducted proteomic and targeted, quantitative metabolomic analyses on heart tissue from patients with HCM and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 61 publications
6
41
0
Order By: Relevance
“…Besides these two major metabolic processes, enhanced ketone body metabolism is also shown in DCM and HCM (56,57). Interestingly, suppressed oxidative metabolism, amino acid metabolism, pentose phosphate pathway, and nucleotide metabolism are observed in DCM (58)(59)(60)(61), whereas they are all elevated in HCM (19,(62)(63)(64)(65). A recent study further examined the metabolic alterations in DCM and HCM hearts as compared to non-failing control hearts at the global transcriptional level and demonstrated impaired metabolic signaling of fatty acids, carbohydrates, and amino acids in both DCM and HCM hearts (66).…”
Section: Shared and Unique Metabolic Alterations Between Dcm And Hcmmentioning
confidence: 99%
“…Besides these two major metabolic processes, enhanced ketone body metabolism is also shown in DCM and HCM (56,57). Interestingly, suppressed oxidative metabolism, amino acid metabolism, pentose phosphate pathway, and nucleotide metabolism are observed in DCM (58)(59)(60)(61), whereas they are all elevated in HCM (19,(62)(63)(64)(65). A recent study further examined the metabolic alterations in DCM and HCM hearts as compared to non-failing control hearts at the global transcriptional level and demonstrated impaired metabolic signaling of fatty acids, carbohydrates, and amino acids in both DCM and HCM hearts (66).…”
Section: Shared and Unique Metabolic Alterations Between Dcm And Hcmmentioning
confidence: 99%
“…Additionally, there has a quantifiable correlation between metabolomics and other omics (genomics, transcriptomics, proteomics, etc. ), such as mRNA count can predict metabolite level, 36 gut bacteria has a correlation with amino acids level in patients with fibromyalgia, 37 the expressions of creatine kinase and mitochondrial protein are consistent with acylcarnitine and acetyl‐CoA in human hypertrophic cardiomyopathy 38 . Moreover, the Human Metabolome Database (https://hmdb.ca/) is a free database containing detailed information of small molecule metabolites in the human body that can be used for metabolomics research, 39 and the corresponding metabolites analysis can be performed by MetaboAnalyst 5.0 (https://www.metaboanalyst.ca/, a free platform for metabolomics analysis) 40 .…”
Section: The Categories Of Omicsmentioning
confidence: 99%
“…However, increased contractility and the resulting higher energy demand must be supported by efficient metabolism. Inefficient energy utilization has been shown to cause energetic stress and adverse remodeling [11] . Two recent multi-omics studies have shown that energy metabolism is impaired in the heart of HCM patients [12,13] .…”
mentioning
confidence: 99%
“…Inefficient energy utilization has been shown to cause energetic stress and adverse remodeling [ 11 ] . Two recent multi-omics studies have shown that energy metabolism is impaired in the heart of HCM patients [ 12 , 13 ] . In particular, increased levels of free fatty acids and reduced acylcarnitines, with broadly downregulated gene expression and protein reduction across fatty acids transport, activation, and β-oxidation, suggest a severely depressed fatty acid metabolism associated with HCM, similar to what have been reported in the advanced heart failure.…”
mentioning
confidence: 99%
See 1 more Smart Citation